A Technique for Measuring Microparticles in Polar Ice Using Micro-Raman Spectroscopy. (27th July 2010) - Sakurai, Toshimitsu; Ohno, Hiroshi; Horikawa, Shinichiro; Iizuka, Yoshinori; Uchida, Tsutomu; Hondoh, Takeo
Abstract : We describe in detail our method of measuring the chemical forms of microparticles in polar ice samples through micro-Raman spectroscopy. The method is intended for solid ice samples, an important point because melting the ice can result in dissociation, contamination, and chemical reactions prior to or during a measurement. We demonstrate the technique of measuring the chemical forms of these microparticles and show that the reference spectra of those salts expected to be common in polar ice are unambiguously detected. From our measurements, Raman intensity of sulfate salts is relatively higher than insoluble dust due to the specific Raman scattering cross-section of chemical forms of microparticles in ice.